Structure-property relationships in nanoporous metallic glasses. (March 2016) - Şopu, D.; Soyarslan, C.; Sarac, B.; Bargmann, S.; Stoica, M.; Eckert, J.
Abstract: We investigate the influence of various critical structural aspects such as pore density, distribution, size and number on the deformation behavior of nanoporous Cu64 Zr36 glass. By using molecular dynamics and finite element simulations an effective strategy to control the strain localization in nanoporous heterostructures is provided. Depending on the pore distribution in the heterostructure, upon tensile loading the nanoporous glass showed a clear transition from a catastrophic fracture to localized deformation in one dominant shear band, and ultimately to homogeneous plastic flow mediated by a pattern of multiple shear bands. The change in the fracture mechanism from a shear band slip to necking-like homogeneous flow is quantitative interpreted by calculating the critical shear band length. Finally, we identify the most effective heterostructure with enhanced ductility as compared to the monolithic bulk metallic glass. The heterostructure with a fraction of pores of about 3% distributed in such a way that the pores do not align along the maximum shear stress direction shows higher plasticity while retaining almost the same strength as the monolithic glass. Our results provide clear evidence that the mechanical properties of nanoporous glassy materials can be tailored by carefully controlling the design parameters. Graphical abstract: